2023
DOI: 10.1111/apt.17623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different PD‐1 inhibitor combination therapies for unresectable intrahepatic cholangiocarcinoma

Abstract: SummaryBackgroundImmune checkpoint inhibitor (ICI) combination therapy offers a new option for treatment of unresectable intrahepatic cholangiocarcinoma (uICC).AimTo compare the effect of different anti‐PD‐1 combination therapies as the first‐line treatments for uICC.MethodsThis study included 318 patients who received chemotherapy alone (Chemo), anti‐PD‐1 plus chemotherapy (ICI‐chemo), anti‐PD‐1 plus targeted therapy (ICI‐target) or anti‐PD‐1 plus targeted therapy and chemotherapy (ICI‐target‐chemo) as first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…All the studies, except that of Lei et al. ( 19 ), reported tumor responses (n = 535). Overall, only 3 patients (0.6%) achieved a complete response (CR), while 182 (34.0%) achieved a partial response (PR), and 230 patients (43.0%) had a stable disease (SD) state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the studies, except that of Lei et al. ( 19 ), reported tumor responses (n = 535). Overall, only 3 patients (0.6%) achieved a complete response (CR), while 182 (34.0%) achieved a partial response (PR), and 230 patients (43.0%) had a stable disease (SD) state.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 15 included studies, there were 5 prospective studies (no randomized controlled trial) (16-18, 24, 25) and 10 retrospective studies (19)(20)(21)(22)(23)(26)(27)(28)(29)(30). All the studies underwent quality appraisal according to the NOS (Supplementary Table 1), with 13 ranked as medium quality, and 2 as high quality.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Studies on the application of pembrolizumab for incurable cholangiocarcinoma in Phase I b and II trials have found that regardless of PD-L1 expression, it can effectively control 6%-13% of advanced bile duct cancers, with manageable toxicity (6).A real-world study based on Phase III clinical trial TOPAZ-1, incorporating durvalumab into the first-line chemotherapy regimen for cholangiocarcinoma, demonstrated a 20% reduction in the risk of death (HR=0.80, 95% CI: 0.66-0.97, P=0.021), confirming the efficacy and safety of durvalumab for cholangiocarcinoma patients (7). Subsequently, more studies and case reports on the application of other immune checkpoint inhibitors in cholangiocarcinoma have emerged, further bolstering the case for immunotherapy in cholangiocarcinoma (8)(9)(10)(11).Currently, the combination of durvalumab with gemcitabine and cisplatin is an option for first-line treatment of locally advanced or metastatic cholangiocarcinoma. However, further research is needed to verify the application of immune checkpoint inhibitors in cholangiocarcinoma and to identify prognostic risk factors for patients receiving immunotherapy.…”
Section: Introductionmentioning
confidence: 87%
“…Finally, over the past few years, advances in precision oncology have driven the development of immuno- and targeted therapies, changing the paradigm of cancer treatment, including BTC, from a population-based perspective to individualised treatment for each patient and tumour. On this basis, enabling translational surgery for unresectable BTC, thereby further enhancing the survival of BTC patients is also a future concern ( 5 ). Although immunotherapy offers great potential for BTC, there are still a majority of patients who still fail to respond well after treatment.…”
mentioning
confidence: 99%